Memahami Stigma Keluarga HIV-AIDS Melalui Straussian Grounded Theory - Amira Esti; Mona Yolanda (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
HIV-AIDS has severe psychological effects on families of sufferers or people living with HIV in seeing themselves and / or other people. HIV-AIDS experienced by someone causes many psychological consequences. Stigma develops through internalization by PLWHA with negative perceptions about themselves and how they put themselves in the perspective of negative views by others towards them. The purpose of this study is to understand how the stigma of HIV-AIDS families in their daily lives. The purpose of this study was to understand the stigma of the HIV-AIDS family (PLWHA) in West Sumatra with a qualitative approach through the Straussian Grounded Theory. This study uses a qualitative method with Strauss's grounded theory approach. Conducted from 2 to 15 July 2018 Methods of data collection in this study are semi-structured interviews, review documents and field notes. Data analysis methods: open coding, axial coding, selective coding. The results of the study found five categories: Denail. Low self-esteem, social isolation, fear and support systems. These categories form a theory and deep understanding of the stigma of families with people with HIV-AIDS. The results of the study can be used as a basis for health workers, especially in providing nursing, education and research services. The results of this study have implications for families, communities, health workers, communities and other relevant parties in an effort to deal with the stigmatization of the HIV-AIDS family. This research is expected to produce output in the form of journal publications in non-accredited scientific journals and textbooksKeywords : self care deficit nursing theory